Mengupayakan Keadilan Bagi Korban Kekerasan Seksual Melalui Aktivisme Tagar: Kesempatan dan Kerentanan di Indonesia - Andi Misbahul Pratiwi (Jurnal Perempuan, 2021)
Digital technology brings new opportunities to accessing justice for women and marginalized groups after being excluded from conventional-masculine technology for decades. In the internet era, the use of social media has become very massive and intensive, therefore feminist activism in this digital space is unavoidable. Hashtag activism has become popular since the #MeToo movement and such an opportunity to seek justice for victims and survivors through voicing and documenting their voices. The use of hashtags (#) opens up opportunities for victims’ stories to be documented, connect with other stories, and go viral. In Indonesia, the use of hashtags in activism also occurs in more local contexts such as #KitaAgni, #SaveIbuNuril, #UIITidakAman, #KamiBersamaKorban, and #SahkanRUUPKS. Some hashtag activism has succeeded in initiating follow-up actions in the offline world, although not always viral stories get satisfactory case resolutions. This study uses a qualitative approach, and collecting the data through literature studies, especially on feminist theories ariund technology and digital such as; Science and Technology Studies (STS) feminism, cyberfeminism, technofeminism, and feminist digital activism. This paper finds that the digital space is a contested space where there are opportunities and vulnerabilities for victims, activists, and netizens to seek justice through hashtag activism.